2007
DOI: 10.1074/jbc.m701641200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase D-mediated Phosphorylation and Nuclear Export of Sphingosine Kinase 2

Abstract: Sphingosine kinase (SPHK) is a key enzyme producing important messenger sphingosine 1-phosphate and is implicated in cell proliferation and suppression of apoptosis. Because the extent of agonist-induced activation of SPHK is modest, signaling via SPHK may be regulated through its localization at specific intracellular sites. Although the SPHK1 isoform has been extensively studied and characterized, the regulation of expression and function of the other isoform, SPHK2, remain largely unexplored. Here we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 44 publications
(48 reference statements)
4
120
1
1
Order By: Relevance
“…In addition, the generation of a 'chimeric' SK-1 containing the NLS of SK-2 at its N-terminus was able to mimic the inhibitory effect on DNA synthesis . Moreover, it was shown that nuclear SK-2 can be phosphorylated by the protein kinase D, which is also known as protein kinase C-m, resulting in export of SK-2 to the cytoplasm (Ding et al, 2007). All these data suggest that there are subcellular pools of sphingolipids and that the knockout of either SK-1 or SK-2 may lead to subcellular and local changes in sphingolipid levels that are not detectable using our total cell lipid extraction method.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, the generation of a 'chimeric' SK-1 containing the NLS of SK-2 at its N-terminus was able to mimic the inhibitory effect on DNA synthesis . Moreover, it was shown that nuclear SK-2 can be phosphorylated by the protein kinase D, which is also known as protein kinase C-m, resulting in export of SK-2 to the cytoplasm (Ding et al, 2007). All these data suggest that there are subcellular pools of sphingolipids and that the knockout of either SK-1 or SK-2 may lead to subcellular and local changes in sphingolipid levels that are not detectable using our total cell lipid extraction method.…”
Section: Discussionmentioning
confidence: 78%
“…Tumor necrosis factor-a triggered phosphorylation of SphK1 by p42/44 MAPK (41), whereas epidermal growth factor induced a protein kinase Cydependent phosphorylation and the subsequent translocation of SphK1 to the plasma membrane (42). Phorbol 12-myristate 13-acetate triggered p42/44 MAPK and protein kinase D to phosphorylate SphK2, thus enhancing its catalytic activity and mediating its nuclear export (25,26). Activation of signaling pathways such as PI3K, extracellular signal-regulated kinase 1/2, or p38 MAPK, which are active under hypoxia (9,40), might therefore add to SphK2 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of SphK2 in response to growth factors or phorbol 12-myristate 13-acetate via activation of extracellular signal-regulated kinase 1 and phosphorylation at Ser 351 and Thr 578 has also been shown (25). Ding et al identified two more serine residues within SphK2 (Ser 419 and Ser 421 ) that became phosphorylated by protein kinase D, which fostered the nuclear export of SphK2 as an alternative regulatory circuit (26).…”
Section: Introductionmentioning
confidence: 99%
“…Human SphK2-GFP and murine S1P 1 -CFP were constructed as described previously 41,50 . Murine S1P 3 was amplified and cloned into pECFP-N1 (Clontech) and pEGFP-N1 (Clontech) for making CFP-or GFP-tagged S1P 3 , respectively.…”
Section: Methodsmentioning
confidence: 99%